2021
DOI: 10.1111/jfpp.15318
|View full text |Cite
|
Sign up to set email alerts
|

Rice‐bran oil: An emerging source of functional oil

Abstract: Rice (Oryza sativa L.) is the major food crops in the world and accounting for around 20% of the dietary energy intake of the global population. Rice bran (RB), the outer brown layer of rice, is one of the main by‐products during milling. It is a rice source of rice‐bran oil (RBO) with good fatty acid profile and phytonutrients like oryzanols, tocopherols, tocotrienols, phytosterols, and importantly dietary fibers. These bioactive compounds possess cardioprotective, anti‐oxidative, anti‐inflammatory, antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 88 publications
1
23
0
Order By: Relevance
“…However, these earlier studies reported no significant difference in FI among the experimental groups [17,34]. The beneficial effects of RBO on the broiler's performance may be due to its bioactive components, including γ-oryzanols, tocopherols, tocotrienols, polyphenols, sterols, and ferulic acid [12,17]. In previous studies, vegetable oil reduced the passage rate…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…However, these earlier studies reported no significant difference in FI among the experimental groups [17,34]. The beneficial effects of RBO on the broiler's performance may be due to its bioactive components, including γ-oryzanols, tocopherols, tocotrienols, polyphenols, sterols, and ferulic acid [12,17]. In previous studies, vegetable oil reduced the passage rate…”
Section: Discussionmentioning
confidence: 88%
“…What places RBO on top of other vegetable oils is its antioxidant components, which have been documented to have an outstanding nutritive significance and are recognized to induce substantial lipid-reducing effects and antioxidant properties based on research performed on mice and humans (see review, 12). Previous studies on the dietary supplementation of RBO in broilers showed enhanced growth performance, improved immune response, and reduced cholesterol concentration [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations